Analyse von Polymorphismen der Interleukine 1, -4, -13 und des Fcgamma-Rezeptors IIa bei Patienten mit aggressiver Parodontitis und einer Gruppe von parodontitisresistenten Probanden - Rathe, Florian; Justus Liebig University Giessen (My University, 2007)
Ziel der Studie war, mögliche genetische Risikofaktoren, wie die Polymorphismen der Interleukine: IL-1 alpha, IL-1 beta, IL-4, IL-13 und des FcgammaRezeptors IIa bei einer Gruppe von parodontitisresistenten Probanden (n=22) zu untersuchen. Diese Gruppe wurde mit einer Gruppe von jungen, gesunden Individuen (n=29) und einer Gruppe von Patienten (n=35), die an einer aggressiven Parodontitis litten, verglichen. Betrachtet man die Verteilung der Häufigkeiten der IL-1 Polymorphismen zwischen den einzelnen Gruppen, so lässt sich kein eindeutiges Verteilungsmuster feststellen, was die Ergebnisse von Gonzales et al. (2003) und Hodge et al. (2001) bestätigt. Das Vorliegen des kombinierten nichtpolymorphen Genotyps von IL-4 könnte mit einer Resistenz (Gruppe der parodontitisre¬sistenten Probanden: 77,3%); das Vorliegen des kombinierten poly¬morphen Genotyps (homozygoter Zustand der polymorphen Allele beider Polymorphismen) könnte mit einer Anfälligkeit (Gruppe der Patienten mit aggres¬siver Parodontitis: 14,3%) gegenüber der aggressiven Parodontitis interpretie¬rt werden. Für den IL-13 Exonpolymorphismus sind leichte Tendenzen erkennbar, so liegt der polymorphe Genotyp (homozygoter Zustand der polymorphen Allele) mit 14,3% für die Gruppe der Patienten mit aggressiver Parodontitis etwas häufiger vor als in der Gruppe der jungen, gesunden Proban¬den mit 10,3% und für die parodontitisresistenten Gruppe mit 9,1%. Der nicht-polymorphe Genotyp des FcgammaRIIa(-H/H131) scheint mit der aggressiven Parodontitis assoziiert zu sein, wohingegen der polymorphe Genotyp des FcgammaRIIa(-R/R131) mit parodontaler Gesundheit, eventuell sogar mit einer Resistenz in Verbindung stehen könnte. Die große Heterogenität der Genotypprofile lässt erkennen wie schwierig eine Aussage über die Wirkung einzelner Polymorphismen auf die Ätiologie der Parodontitis ist. Des Weiteren können die Ergebnisse dieser Studie aufgrund der geringen Probandenzahl nicht auf größere Populationen übertragen werden.

The aim of the present study was to determine possible genetic risk factors such as Polymorphisms of the IL-1alpha, IL-1beta, IL-4, IL-13 and Fcgamma receptor IIa genes in a group of periodontitis resistant subjects (n=22). This group was compared with a group of young, healthy subjects (n=29) and a group of young subjects suffering from aggressive periodontitis (n=35). With regard to the distribution of the IL-1alpha and IL-1beta polymorphisms in the groups, the results of the present investigation corroborate the findings of Gonzales et al. (2003) and Hodge et al. (2001) who failed to show an association between these IL-1 polymorphisms and aggressive periodontitis. Within the limits of the present study, it might be suggested that the combination of the wild type alleles of the IL-4 polymorphisms may be associated with a resistance to periodontal destruction (periodontitis resistant group: 77.3%), whereas the combination of the mutant alleles in both IL-4 polymorphisms may be associated with susceptibility to aggressive periodontitis (aggressive periodontitis group: 14.3%). With regard to the frequencies of the IL-13 Exon-polymorphism between groups, there was a tendency of a different distribution. The genotype containing the both rare alleles occurred in the groups of healthy subjects (10.3% in young, healthy subjects and 9.1% in periodontitis resistant subjects) slightly less frequent than in patients with aggressive periodontitis (14.3%). The results of the present study further indicate that the H/H 131 genotype of the Fcgamma-RIIa is in association with aggressive periodontitis, whereas the FcgammaIIa(-R/R131) may be associated with periodontal health, possibly even with resistance to periodontitis. Finally, the data of the genotype profiles showed that due to the huge heterogeneity between the genotypes of each subject, it is very difficult to draw conclusions of the role of single polymorphisms in the etiology of periodontitis.
Analysis of polymorphisms of the Interleukin 1, -4, -13 and the Fcgamma receptor IIa in patients suffering from aggressive periodontitis and a group of periodontitis resistant subjects
Keywords: Polymorphismen; aggressive Parodontitis; parodontitisresistent; polymorphism; aggressive periodontitis; periodontitis resistance; ddc:610